Revised douglas method for rare earth element extraction processes: A case study of extraction from Malaysian monazite sand - Farouq, Ahmat; Mohd Yusri, Mohd Yunus (AIP Publishing, 2023)
The rare earth elements have become greatly important in the development of advanced technology, but the challenge lies in the extraction of the elements where the process is arduous and complex. There is an unavailability of a systematic acumen-based approach for the extraction of rare earth elements. This paper presents a revised work of the hierarchical approach based on the Douglas model to develop a superstructure of a conceptual design for the extraction of rare earth elements. Douglas model was originally authored for the development of a systematic conventional chemical process, particularly petrochemical industry and when the model is used to design rare earth element extraction systems, there are numbers of limitations to suit the extraction. The limitations are due to the nature of the rare earth elements extraction is different from the conventional chemical process. Other limitations are a variety of feedstock, unknown stoichiometry, the presence of impurities and radioactive material and the process is extremely lengthy. To overcome these limitations, a revision of the model is proposed and this revised model is discussed on each hierarchical level. A case study of the extraction of rare earth elements from Malaysian monazite sand by using a revised Douglas model is discussed.